Phytochemical Profile and Apoptotic Activity of Onopordum cynarocephalum - Formisano, Carmen; Rigano, Daniela; Russo, Alessandra; Cardile, Venera; Caggia, Silvia; Apostolides Arnold, Nelly; Mari, Angela; Piacente, Sonia; Rosselli, Sergio; Senatore, Felice; Bruno, Maurizio (Planta Medica, 2012)
A phytochemical investigation of acetone and chloroform extracts of the aerial parts of Onopordum cynarocephalum Boiss. et Blanche was carried out. It led to the isolation of two new sesquiterpenes, the elemane aldehyde (2) and the eudesmane (11), together with 15 known compounds: two lignans (1 and 15) and 13 sesquiterpenes (3–10, 12–14, 16, 17). The structures were elucidated by spectroscopic analyses, especially 1D and 2D NMR spectra. The anti-growth effect against three human melanoma cell lines, M14, A375, and A2058, of the different extracts and compounds of O. cynarocephalum was also investigated. Among them, the chloroform extract exhibited the strongest biological activity, while the most active compounds were the lignan arctigenin (1), and the sesquiterpenes, compounds 3, 5, and 6 belonging to the elemane type, and 7 belonging to the eudesmane type. Our data also demonstrate that acetone and chloroform extracts induce, in the A375 cell line, apoptotic cell death that could be related to an overall action of the compounds present, but in particular to the lignans arctigenin (1) and the sesquiterpenes compounds 3–8 and 16. In fact, these molecules were able to induce a high DNA fragmentation, correlated to a significant increase of the caspase-3 enzyme activity. Furthermore, apoptosis appears to be mediated, at least in part, via PTEN activity and the inhibition of Hsp70 expression.
Keywords: Onopordum cynarocephalum; Asteraceae; sesquiterpenes; melanoma; apoptosis; heat shock protein 70